A molecular crowding thermo-switchable chiral G-quartet hydrogel with circularly polarized luminescence property. Issue 16 (12th April 2022) - Gao, Chenqi; Zhang, Zhiwei; Zhang, Xinying; Chen, Jingqi; Chen, Yingying; Zhao, Chuanqi; Zhao, Lijuan; Feng, Lingyan
Abstract : A molecular crowding chiral G-quartet hydrogel with thermo-switchable CPL property. Abstract : A novel helix hydrogel with a G-quartet structure was synthesized from guanosine (Gua) and its derivative 5′-guanosine monophosphate (5′-GMP) under a molecular crowding environment. The chirality of the hydrogel is adjusted by controlling the gelling speed. The chiral hydrogel can induce an achiral dye Thioflavin T (ThT) to realize circularly polarized fluorescence (CPL). The CPL dissymmetry factor | g lum | of the dye-hydrogels can reach 3 × 10 −2 and can be switched easily.